Ethnic differences and heterogeneity in genetic and metabolic makeup contributing to nonalcoholic fatty liver disease - Krisztina Szántó; Jiawei Li; Pául Cordero; Jude A. Oben (2019)
Abstract: Obesity is the most prevalent noncommunicable disease in the 21st century, associated with triglyceride deposition in hepatocytes leading to nonalcoholic fatty liver disease (NAFLD). NAFLD is now present in around a third of the world's population. Epidemiological studies have concluded that ethnicity plays a role in complications and treatment response. However, definitive correlations of ethnicity with NAFLD are thoroughly under-reported. A comprehensive review was conducted on ethnic variation in NAFLD patients and its potential role as a crucial effector in complications and treatment response. The highest NAFLD prevalence is observed in Hispanic populations, exhibiting a worse disease progression. In contrast, African-Caribbeans exhibit the lowest risk, with less severe steatosis and inflammation, lower levels of triglycerides, and less metabolic derangement, but conversely higher prevalence of insulin resistance. The prevalence of NAFLD in Asian cohorts is under-reported, although reaching epidemic proportions in these populations. The most well-documented NAFLD patient population is that of Caucasian ethnicity, especially from the US. The relative paucity of available literature suggests there is a vital need for more large-scale multi-ethnic clinical cohort studies to determine the incidence of NAFLD within ethnic groups. This would improve therapy and drug development, as well as help identify candidate gene mutations which may differ within the population based on ethnic background. Keywords: NAFLD, steatosis, obesity, ethnicity, steatohepatitis